Educating Guidelines on Balanced Nutrition and Anemia in Teenage Girls Aged 12-19 Years With Leaflet Media in SMK Ekonomika of UPTD Puskesmas Limo Work Area Depok City in 2023: Penyuluhan Pedoman Gizi Seimbang dan Anemia Pada Remaja Putri Usia 12-19 Tahun Dengan Media Leaflet di SMK Ekonomika Wilayah Kerja UPTD Puskesmas Limo Kota Depok Tahun 2023 - Karmila, Nisa; Marjan, Avliya Quratul (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Background: Teenagers are in the age range of 10-19 years. Teenage girls are a group that is vulnerable to problems related to nutrition, including anemia wich can be caused by diet and physical activity. The prevalence of anemia in Depok in 2019 being 16.42%. Based on 2018 Riskesdas data, out of 80.9% of iron supplement coverage in middle and high schools, 20,5% of young women felt there was no need to finish or consume iron supplement. Purpose: this activity aims to examine the factors that influence nutritional status and anemia in teenage girls aged 12-19 years in the UPTD Puskesmas Limo, Depok work area. Method: Education was carried out after completing the pre-test using leaflets for 30 female students at SMK Ekonomika, then continued with completing the post-test. Results: the results obtained from this activity were an increase in post-test scores ≥60 by 70%. The results obtained from the Wilcoxon test are Sig. values, 0.000 <0.05. Conclusion: the conclusion of the tests carried out is that there is a difference in knowledge regarding balanced nutrition guidelines and anemia before and after the education was carried out. Abstrak Latar belakang: remaja berada pada rentang usia 10-19 tahun. Remaja putri merupakan kelompok yang rentan terhadap permasalahan gizi, termasuk anemia yang dapat disebabkan oleh pola makan dan aktivitas fisik. Prevalensi anemia di Kota Depok pada tahun 2019 sebesar 16.42%. Berdasarkan data Riskesdas tahun 2018, dari 80.9% cakupan suplemen zat besi di SMP dan SMA, 20.5% remaja putri merasa tidak perlu menghabiskan atau mengkonsumsi tablet tambah darah. Tujuan: kegiatan ini bertujuan unutk mengetahui faktor-faktor yang mempengaruhi status gizi dan anemia pada remaja putri usia 12-19 tahun di wilayah kerja UPTD Puskesmas Limo, Depok. Metode: Edukasi dilaksanakan setelah peserta menyelesaikan pra-tes menggunakan leaflet kepada 30 siswi SMK Ekonomika, kemudian dilanjutkan dengan menyelesaikan pasca-tes. Hasil: hasil yang diperoleh dari uji Wilcoxon adalah nilai Sig 0.000 <0.05. Kesimpulan: kesimpulan dari tes yang dilakukan adalah terdapat perbedaan pengetahuan tentang pedoman gizi seimbang dan anemia saat sebelum dan sesudah dilakukan edukasi.